Impact of the application of neurolinguistic programming to mothers of children enrolled in a day care center of a shantytown - Miranda, Cláudio Torres de; Paula, Cristiane Silvestre de; Palma, Domingos; Silva, Edina Mariko Koga da; Martin, Denise; Nóbrega, Fernando José de (São Paulo Medical Journal, 1999)
CONTEXT: Of the members of a family, the mother is without doubt the most important one, which provides justification for including an evaluation of her mental health as one of the variables to be considered as determining factors in each child’s level of development. OBJECTIVE: To assess the impact of the application of Neurolinguistic Programming (NLP) on child development, home environment and maternal mental health. DESIGN: Randomised controlled trial. SETTING: The study included children enrolled in the municipal day care center of a shantytown in the City of São Paulo. PARTICIPANTS: 45 pairs of mothers and respective children between 18 and 36 months of age. MAIN MEASUREMENTS: Children’s development (Bayley scales); home environment variation (HOME); and maternal mental health (SRQ). Comparison between before and after the intervention was made in terms of children’s psychomotor development, home environment and maternal mental health. INTERVENTION: Application of the NLP technique to the experimental group and comparison with a control group. 1 - Experimental (EG), consisting of 23 children submitted to intervention by NLP; and 2 - Control (CG), with 22 children with no intervention. Length of intervention: 15 sessions of NLP. RESULTS: 37 children remained in the study (EG = 10, CG = 27). Variations in mental development (OR 1.21, IC 95% 0.0 to 23.08) in their home environment (Wilcoxon): p = 0.96 (before) and p = 0.09 (after); in maternal mental health: p = 0.26, 2 df. CONCLUSIONS: There was a trend that indicated positive effects on the home environment from the intervention.